Implementing Net-Talk in FTMSK / Mohd Hizzol Mohd Yusof - Mohd Yusof, Mohd Hizzol (Faculty of Information Technology and Quantitative Sciences, 2005)
This project is about implementation Net-Talk (Video Conferencing) in Faculty of Information Technology & Quantitative Science (FTMSK), UiTM Shah Alam. This project is focusing on one to one (1 - 1) communication and implement in Local Area Network (LAN) in FTMSK. This project allows virtual communication between student with lecturer and vice versa. The main purpose of the implementation is to propose a live video conferencing and as a new method for student to virtually meet lecturer without having to attend to the lecturer room. This has been accomplished through the use of appropriate methodologies by distributing questionnaires. The finding of this project has proven that the video conferencing is possible to be taken into consideration.